Ligand-Induced Donor State Destabilisation – A New Route to Panchromatically Absorbing Cu(I) Complexes - Tran, Jens H.; Traber, Philipp; Seidler, Bianca; Goerls, Helmar; Gräfe, Stefanie; Schulz, Martin (Chemistry - A European Journal, 2022)
The intense absorption of light to covering a large part of the visible spectrum is highly desirable for solar energy conversion schemes. To this end, we have developed novel anionic bis(4H-imidazolato)Cu(I) complexes (cuprates), which feature intense, panchromatic light absorption properties throughout the visible spectrum and into the NIR region with extinction coefficients up to 28,000 M−1 cm−1. Steady-state absorption, (spectro)electrochemical and theoretical investigations reveal low energy (Vis to NIR) metal-to-ligand charge-transfer absorption bands, which are a consequence of destabilized copper-based donor states. These high-lying copper-based states are induced by the σ-donation of the chelating anionic ligands, which also feature low energy acceptor states. The optical properties are reflected in very low, copper-based oxidation potentials and three ligand-based reduction events. These electronic features reveal a new route to panchromatically absorbing Cu(I) complexes.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ab initio calculations; cuprates; electrochemistry; N ligands; UV/Vis spectroscopy